Effect size: calculation using a visual basic module - Dominguez Lara, Sergio Alexis (2013)
This paper presents a module in Visual Basic to calculate the effect size. Proper use of this method and its failure to implement in traditional statistical packages justifies the construction of software as a tool for research in psychology, where it is common to use the statistically significant difference as a unique indicator of the magnitude and importance of difference between groups, without considering other conceptual and technical aspects that are necessary to understand more deeply such comparisons and the implications of these. Use and limitation of the tool are in discussion.